Application of direct PCR for phylogenetic analysis of Fusarium fujikuroi species complex isolated from rice seeds - Jeon, Hosung; Kim, Jung-Eun; Yang, Jung-Wook; Son, Hokyoung; Min, Kyunghun (Frontiers in Plant Science, 2023)
Plant pathogenic fungi cause severe yield losses and mycotoxin contamination in crops. The precise and rapid detection of fungal pathogens is essential for effective disease management. Sequencing universal DNA barcodes has become the standard method for the diagnosis of fungal diseases, as well as for identification and phylogenetic analysis. A major bottleneck in obtaining DNA sequence data from many samples was the laborious and time-consuming process of sample preparation for genomic DNA. Here, we describe a direct PCR approach that bypasses the DNA extraction steps to streamline the molecular identification of fungal species. Using a direct PCR approach, we successfully sequenced the nuclear ribosomal internal transcribed spacer (ITS) region for the representatives of major fungal lineages. To demonstrate the usefulness of this approach, we performed a phylogenetic analysis of the Fusarium fujikuroi species complex, which causes bakanae (“foolish seedling”) disease of rice and mycotoxin contamination. A total of 28 candidate strains were isolated from rice seeds in the Republic of Korea, and the identity of the isolates was determined using the DNA sequence of both ITS and translation elongation factor 1-α regions. In addition, 17 F. fujikuroi isolates were examined for fumonisin (FB) production in rice medium using an enzyme-linked immunosorbent assay. Phylogenetic and toxigenic analyses showed that the F. fujikuroi strains could be distinguished into two groups: FB producers (B14-type) and non-producers (B20-type). These results will accelerate the molecular identification of fungal pathogens and facilitate the effective management of fungal diseases.